Zakat expenditure, school enrollment, and economic growth in Malaysia - Yusoff, Mohammed (Center for Promoting Ideas (CPI), 2011)
The main objective of this study is to determine the impact of zakat spending and school enrollment on economic growth using panel data represented by the fourteen states of Malaysia. Zakat is collected and disbursed to the eight groups of eligible recipients by each state in Malaysia. Malaysia also has been one of the developing countries that has given a special attention on education to provide the man-power and skills needed by the various sectors of the economy. As a result, there has been a large increase in the enrollment of students in both primary and secondary schools as well as in tertiary education. The results of this study support the hypothesis that zakat spending and school enrollment are important determinants of economic growth in Malaysia. The zakat spending and student enrollment could significantly explain the variation in the growth of real output represented by the growth in real GDP. Therefore, it is suggested that all Muslim countries must improve the efficiency of zakat collection and spend it prudently. A more serious effort has to be made to formulate better strategies, planning, and effective policy actions to provide the needed infrastructure and to increase the stock of human capital in accordance to the need of the nations to generate growth and sustain the development of Muslim society.